2014
DOI: 10.1063/1.4900657
|View full text |Cite
|
Sign up to set email alerts
|

Free-energy calculations for semi-flexible macromolecules: Applications to DNA knotting and looping

Abstract: We present a method to obtain numerically accurate values of configurational free energies of semiflexible macromolecular systems, based on the technique of thermodynamic integration combined with normal-mode analysis of a reference system subject to harmonic constraints. Compared with previous free-energy calculations that depend on a reference state, our approach introduces two innovations, namely, the use of internal coordinates to constrain the reference states and the ability to freely select these refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 93 publications
0
21
0
Order By: Relevance
“…. In the Partition Function and Free Energy for a Circular Chain section, we discuss the numerical computation of the partition function Q cir for a circular chain using the TI‐NMA method and obtain the corresponding NMA result Q cir (NMA). In the Comparison of J‐Factor Values Obtained by NMA and TI‐NMA section, we obtain the J factor, J, as a universal function of L/P and compare the exact result for J with the corresponding NMA result, JNMA.…”
Section: Theory and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…. In the Partition Function and Free Energy for a Circular Chain section, we discuss the numerical computation of the partition function Q cir for a circular chain using the TI‐NMA method and obtain the corresponding NMA result Q cir (NMA). In the Comparison of J‐Factor Values Obtained by NMA and TI‐NMA section, we obtain the J factor, J, as a universal function of L/P and compare the exact result for J with the corresponding NMA result, JNMA.…”
Section: Theory and Resultsmentioning
confidence: 99%
“…where the elastic constants cb, cs are the same as in the Partition Function for a Linear Chain section. We compute the partition function Q cir and the free energy Fcir=kBTlntrue(Q cirtrue) using the TI‐NMA method presented in reference and summarized for the present case in Figure . In this method, a circular molecular state, C, is gradually transformed into a harmonically constrained reference state C0, which corresponds to the minimum energy conformation.…”
Section: Theory and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, switching the counterion environment can change the twist/writhe partition in supercoiled DNA. Electron microscopy, atomic force microscopy (AFM) (Bednar et al 1994; Bussiek et al 2003; Cherny and Jovin 2001; Shlyakhtenko et al 2003) and computer modelling at the both the polymer (Giovan et al 2014; Schlick et al 1994; Zheng and Vologodskii 2009) and atomistic level (but within a continuum solvent approximation) (Mitchell and Harris 2013) has shown that positively charged counterions promote the compaction of supercoiled DNA into complex topologies in supercoiled plasmids.…”
Section: Dna Counterions and Topologymentioning
confidence: 99%